Vision 2020:Towards an environmentally sound and sustainable development of freshwater resources in Malaysia. - Ho, S.C. (1995)
Malaysia became an independent nation in 1957. At independence its population stood at 6.3 million. Today it is about 18.3 million and this figure has been projected to reach 32 million by the year 2020. Over the last 20 years, the country has developed rapidly as a result of careful economic restructure.